THU0021 IDENTIFICATION OF MUSCLE ASSOCIATED KEY GENES TO SUPPORT AXIAL SPONDYLOARTHRITIS DIAGNOSIS BY TRANSCRIPTOMIC APPROACH, THE MYOSPA STUDY. (13th June 2020) - Mashayekhi Sardoo, A.; Sobral, D.; Domingues, L.; Rodrigues-Manica, S.; Pinheiro Torres, R.; Neto, A.; Alves, P.; Costa, J.; Grosso, A. R.; Branco, J.; Pimentel Dos Santos, F.
Abstract : Background: Early diagnosis of axial Spondyloarthritis (axSpA) represents a major clinical challenge nowadays. Increasing evidence has determined that early diagnosis, prompt treatment initiation and early achievement of remission are the best predictors of long-term clinical, functional and radiographic outcomes. New tools to support the diagnosis are needed. Objectives: This study aims to identify differentially expressed genes that may improve the current clinical diagnosis approach for early axSpA. Methods: A cross-sectional study was conducted on 50 participants, 25 patients with axSpA (according to ASAS criteria) and 25 Healthy Controls, matched by gender, age and levels of physical activity. Peripheral blood samples were collected and RNA-Seq technology was performed. Normalization of raw data, and identification of differentially expressed genes was obtained using edgeR and limma-voom R packages. Gene Set Enrichment Analysis (GSEA) and Functional Enrichment analysis using Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) annotations were also performed. A number of Differently Expressed Genes were highlighted. Results: 311 genes were identified as being significantly differentially expressed between patients and controls. In details, 129 downregulated (7 genes have fold change more than 1) and 182 upregulated genes (3 genes have fold change more than 1) are highlighted. These genes are mostly involved in Myogenesis, Innate Immune Signalling and JAK/STAT pathways. Several genes with functions of skeletal muscle development and muscle contraction were identified. Conclusion: The evidence disclosed that regulation of muscle development and contraction may be also engaged in physiopathology mechanisms of axSpA. These new cues open new perspectives for diagnosis and therapeutic approaches in axSpA. Acknowledgments: To all patients and healthy people who participate in MyoSpA study Disclosure of Interests: Atlas Mashayekhi Sardoo: None declared, Daniel Sobral: None declared, Lucia Domingues: None declared, Santiago Rodrigues-Manica Speakers bureau: Jansse, MSD, Novartis, Rita Pinheiro Torres: None declared, Agna Neto: None declared, Patricia Alves: None declared, Julia Costa: None declared, Ana Rita Grosso: None declared, Jaime Branco Speakers bureau: Vitoria, Fernando Pimentel dos Santos Speakers bureau: Novartis, Pfizer, Biogen, Vitoria,